2011
DOI: 10.1007/s00432-011-1092-z
|View full text |Cite
|
Sign up to set email alerts
|

The SUVmax (maximum standardized uptake value for F-18 fluorodeoxyglucose) and serum squamous cell carcinoma antigen (SCC-ag) function as prognostic biomarkers in patients with primary cervical cancer

Abstract: Higher pretreatment SUVmax of primary tumor indicated worse prognosis, and the prognosis of patients with higher pretreatment SUVmax plus PLN metastasis was even worse both in patients of squamous cell carcinoma (SCC) and non-SCC of cervix. As for patients with SCC of cervix, higher pretreatment serum SCC-ag not only predicted worse prognosis but also predicted disease recurrence in the posttreatment surveillance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 46 publications
1
21
1
2
Order By: Relevance
“…Similar to our study, Pan et al 5 found that SUVmax of primary cervical cancer was not associated with preoperative SCC-ag levels. Pan et al did find that the higher the SUVmax of primary cancer, the poorer the prognosis.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to our study, Pan et al 5 found that SUVmax of primary cervical cancer was not associated with preoperative SCC-ag levels. Pan et al did find that the higher the SUVmax of primary cancer, the poorer the prognosis.…”
Section: Discussionsupporting
confidence: 91%
“…23 Recently, degree of FDG uptake on PET images was shown to be an independent prognostic factor in CC by accumulating evidence. 12,15,17,21 However, there have been conflicting results, and some studies found no significant association between PET results and prognosis. 11,13 Thus, we undertook this meta-analysis to evaluate the prognostic value of 18F-FDG PET or PET/CT in CC.…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed 58 studies in full text, and 45 of them were excluded; the reasons for exclusion are listed in figure 1. Consequently, a total of 1,196 patients from 13 trials [5,6,11,12,13,14,15,16,17,18,19,20,21] were entered into the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%